Prevalence and Factors Associated with Impaired Maternal–Infant Bonding among Mothers Attending Young Child Clinic in Kampala, Uganda - Tukamushabe, Phionah; Ngabirano, Tom Denis; Okonya , Joyce Nankumbi; Saftner, Melissa A. (International journal of environmental research and public health, 2024)
Impaired maternal–infant bonding can have a negative impact on the mother–infant relationship, affecting the social, emotional, and cognitive development of a child. In Uganda, there is a paucity of literature on impaired maternal–infant bonding. This quantitative, cross-sectional study aimed to determine the prevalence and factors associated with impaired maternal–infant bonding. Postnatal mothers (n = 422) attending the Young Child Clinic at Kawempe National Referral Hospital participated in the study. Maternal–infant bonding was measured using the Postpartum Bonding Questionnaire (PBQ). Participants with a score ≥ 13 on the PBQ were considered to have impaired maternal–infant bonding. The prevalence of impaired maternal–infant bonding among mothers was 45% (190/422). Logistic regression was used to determine factors associated with impaired maternal–infant bonding. Unmarried mothers (AOR = 2.05, 95% [CI = 1.03–4.09], p = 0.041), unplanned pregnancy (AOR = 5.19, 95% [CI = 3.07–8.82], p < 0.001), first-time mothers (AOR = 2.46, 95% [CI = 1.37–4.43], p = 0.003), female infant (AOR = 1.80, 95% [CI = 1.13–2.86], p = 0.013), mothers with no/low education levels (AOR = 2.29, 95% [CI = 1.05–4.50], p = 0.036), and those who delivered post term (AOR = 2.49, 95% [CI = 1.10–5.67], p = 0.028) were more likely to have impaired maternal–infant bonding. Nurses and midwives in postnatal care should include maternal–infant bonding within their client’s assessment and provide supportive mother-centered care. Interventions to improve maternal–infant bonding should be created and implemented in clinical practice.